DEVELOPMENT OF ETHNOMATHEMATICS BASED DIGITAL LEARNING MEDIA ON THE SARON MUSICAL INSTRUMENT - Muslimah, Nur Annisa; Hotiah, Herera; Aminah, Neneng; Ferdianto, Ferry (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
Mathematics learning is still separated from local culture, and the concept of ethnomathematics is rarely applied in education, particularly in the context of traditional musical instruments. This research is essential to implement to present contextual and meaningful learning media through a cultural approach. This study aims to develop and assess the feasibility of the GEETNOSAR (Google Sites Ethnomathematics Saron) learning media. This research employs the R&D (Research & Development) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study consisted of 32 eleventh-grade students at SMAN 1 Cilimus. The data collection techniques used in this research are questionnaires, interviews, observations, and documentation.. Based on the research results, it was concluded that the GEETNOSAR learning media was successfully developed and received a score with very valid criteria based on assessments from media experts, content experts, and student responses, amounting to 92.5%. Thus, GEETNOSAR has proven to be suitable for use as contextual and engaging mathematics learning media. It can serve as an innovative learning tool that integrates the potential of local culture with advancements in digital technology, thereby providing meaningful learning experiences for students.